Can Marine Wildlife Tourism Provide an "Edutaining" Experience?. Issue 6 (23rd July 2016) - Pratt, Stephen; Suntikul, Wantanee
ABSTRACT: Marine-based tourism can be both an entertaining and educational experience for tourists – "edutainment". This research surveys participants of a dolphin watching program in Fiji to assess their motives to participate in dolphin watching. The research also examines the extent to which education and enjoyment of the marine wildlife tourism experience can contribute to intended pro-environmental behavior. The study reveals there is moderate evidence to support the hypothesis. Although the educational aspect of the trip was limited, satisfaction with the experience was high. However, there is an opportunity for increased education and interpretation in the context of the experience.